PENGARUH INDIKATOR KEUANGAN TERHADAP RETURN ON EQUITY PADA PERUSAHAAN PUBLIK SEKTOR ENERGI DI INDONESIA - uhti nuarika (Faculty of Economics and Business | Universitas Diponegoro, 2021)
This study aims to determine the financial indicators that have a significant effect on the return on equity (ROE) of the Indonesian energy industry. The literature shows that companies that benefit from higher ROE ratios usually have several competitive advantages that can bring greater profits and thus greater returns for investors. In this case, it seems necessary to determine and study the factors that have the greatest influence on ROE. This study conducted a sample survey of 45 Indonesian energy industry companies listed on the Indonesia Stock Exchange. To determine the strongest ROE driver, we used a linear regression model. Other financial ratios are introduced in this study. Therefore, this study involves the use of five indicators/tariffs that are considered to have a significant effect on ROE. According to our results, asset turnover ratio, financial leverage, and current ratio (Quent Ratio) are the most relevant ratios for determining ROE, which indicates that asset turnover ratio and price have the greatest influence on earnings.